2022
DOI: 10.1016/j.jsxm.2022.03.555
|View full text |Cite
|
Sign up to set email alerts
|

019 Contemporary Nationwide Estimates and Socio-Demographic Associates of Bottom Gender Affirmation Surgical Procedures Among Transgender Persons with Gender Dysphoria

Abstract: Introduction There is paucity of data for transgender persons who undergo genital or bottom gender-affirming surgery (GAS). Objective To provide nationwide estimates of frequency, length of stay, charges, and mortality for bottom GAS hospitalizations among transgender persons diagnosed with gender dysphoria and to characterize socio-demographic, clinical, and hospital-related characteristics of transgender persons with gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Additionally, insurance and lack of healthcare access remain historical obstacles to gender-affirming and mental health treatments in the US ( 9 , 15 ). Slaughter and colleagues studied bottom/genital gender-affirming surgery rates among transgender individuals with gender dysphoria ( 19 ). Researchers found that transgender patients with gender dysphoria are more likely to have gender-affirming surgery if they have private insurance, have fewer comorbidities, and are mainly from the Western US ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, insurance and lack of healthcare access remain historical obstacles to gender-affirming and mental health treatments in the US ( 9 , 15 ). Slaughter and colleagues studied bottom/genital gender-affirming surgery rates among transgender individuals with gender dysphoria ( 19 ). Researchers found that transgender patients with gender dysphoria are more likely to have gender-affirming surgery if they have private insurance, have fewer comorbidities, and are mainly from the Western US ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Slaughter and colleagues studied bottom/genital gender-affirming surgery rates among transgender individuals with gender dysphoria ( 19 ). Researchers found that transgender patients with gender dysphoria are more likely to have gender-affirming surgery if they have private insurance, have fewer comorbidities, and are mainly from the Western US ( 19 ). Further, such procedures typically happen at urban hospitals and, on average, cost $101,654 ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations